2018
DOI: 10.1007/978-3-319-75208-2_12
|View full text |Cite
|
Sign up to set email alerts
|

Fault Analysis of the ChaCha and Salsa Families of Stream Ciphers

Abstract: Abstract. We present a fault analysis study of the ChaCha and Salsa families of stream ciphers. We first show that attacks like differential fault analysis that are common in the block cipher setting are not applicable against these families of stream ciphers. Then we propose two novel fault attacks that can be used against any variant of the ciphers. We base our attacks on two different fault models: the stuck-at fault model and the biased fault model. Each of them is exploited differently by the attacker. If… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The potential weakness is seen to be the rotational XOR probability which increases in other Chacha20 variants. An analysis for fault in Chacha and Salsa stream cipher by [54] shows commonality in differential attacks. From this study, fault model attacks are suggested, and it is seen that when the attacker knows the plaintext and the ciphertext, then the fault mode can easily be exploited; however, the low complexity of this study showed that it is practical in nature [54].…”
Section: Comparison With Existing Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential weakness is seen to be the rotational XOR probability which increases in other Chacha20 variants. An analysis for fault in Chacha and Salsa stream cipher by [54] shows commonality in differential attacks. From this study, fault model attacks are suggested, and it is seen that when the attacker knows the plaintext and the ciphertext, then the fault mode can easily be exploited; however, the low complexity of this study showed that it is practical in nature [54].…”
Section: Comparison With Existing Studiesmentioning
confidence: 99%
“…It is important to note that the motivation for exploring the extended rounds for Chacha20 is based on the limitations that have been identified in other ciphers, as shown in Table 5. These limitations include issues such as weaknesses in the key schedule and the susceptibility of some ciphers to sidechannel attacks [47], attacking QR − F s from keystream [48], QR − F modification, weaknesses in rotational XOR in Chacha20 variants, etc [49], [50], [51], [54]. EChacha20 has been designed to address the specific limitation of improved QR − F and stands to provide a more secure and efficient encryption algorithm.…”
Section: Comparison With Existing Studiesmentioning
confidence: 99%
“…Normally, DFA/AFA on stream ciphers is considered difficult to carry out in practice, compared to block ciphers, as the analysis complexity often goes beyond the computational requirements of automated tools such as satisfiability (SAT) solvers. One may check eSTREAM finalist SALSA or its variant CHACHA in this regard [BGV17].…”
Section: Differential Fault Attack (Dfa)mentioning
confidence: 99%
“…In general, DFA aims at attacking non-linear instructions. Up to now, there have been various attacks exploiting the following operations: bitwise AND [TBM14], bitwise OR [BHL18], addition [TBM14,JB15,BGV17], and table lookup [Riv09a, JLSH13, TM09], often used for Sbox calculation. Even though the attack varies for different ciphers, the main principle behind the attack of a particular operation stays the same [JT12].…”
Section: Attacks On Target Instructionsmentioning
confidence: 99%